The Non-halogenated flame retardant handbook - Morgan, Alexander B.; Wilkie, Charles A., 1941- (Scrivener Publishing ; Wiley, 2014)
Due to the emphasis on replacing halogenated flame retardants with alternate technologies, this handbook contains in one place all of the current commercial non-halogenated flame retardant technologies, as well as experimental systems near commercialization. This book focuses on non-halogenated flame retardants in a holistic but practical manner. It starts with an overview of the regulations and customer perceptions driving non-halogenated flame retardant selection over older halogenated technologies. It then moves into separate chapters covering the known major classes of non-halo.